Analisis Kemampuan Siswa dalam Mengolah Data Sederhana pada Pembelajaran Matematika Dasar Pendidikan Madrasah Ibtidaiyah - Liza Syahputri; Riska Ghusalia; Rauzatul Syahira; Riva Ridhayani (JURNAL MathEdu (Mathematic Education Journal), 2026)
This study aims to analyze the ability of MIN students in processing simple data in basic mathematics learning. The selection of this topic is based on the importance of data processing skills as a foundation for understanding statistics from an early age, yet many students still face difficulties in presenting and interpreting data. The research method used is a qualitative approach with a descriptive type. The subjects of this study were MIN students, and the data were collected through observation, tests, and documentation. The results show that students' ability in processing simple data is at a moderate level. Some students are able to present data in the form of tables, but still have difficulties in understanding and interpreting data accurately. These findings indicate the need for more innovative and interactive learning strategies. Therefore, this study is important as a basis for improving mathematics learning, especially in data processing material, Complexity students’ ability, data processing, basic mathematics, MIN